DAMPAK PENGELOLAAN KEUANGAN PADA KINERJA PELAKU WIRAUSAHA DI DESTINASI WISATA DANAU CIPONDOH - Heny Ratnanningtyas; Amrullah Amrullah; Ismeth Emier Osman (JURNAL KEPARIWISATAAN, 2023)
This study aims to determine the financial management of the performance of entrepreneurs in the tourist destination of Lake Cipondoh. This type of research is descriptive quantitative with multiple regression analysis methods. The sampling technique used a saturated sampling technique because the population and sample were the same, amounting to sixty-three entrepreneurs in Lake Cipondoh. The results showed that partial financial planning, financial records, and separation of personal finance and business finance significantly affected the entrepreneurs' performance. The application of financial planning can save costs which can increase operating profits and have an impact on the performance of entrepreneurs. Financial records can provide information about financial statements so that they can improve the performance of entrepreneurs. Furthermore, the separation of personal finance and business finance will not reduce business capital, so it can improve the performance of entrepreneurs. It was expected that entrepreneurs in Lake Cipondoh tourist destinations: (1) Always implement financial planning to minimize costs and increase profits; (2) Always carry out financial records so that it can be seen that the business carried out has increased or decreased; (3) Always separate business finances from personal finances, to know for sure the total income and net profit.